Development of Waw Mdp Client Record Management System - Mohd Noor, Siti Nur Shahiba; Samsudin, Noor Azah (Applied Information Technology And Computer Science, 2022)
Waw Mdp Services Sdn Bhd is a construction project consultancy company in Kelantan. Due to the manual process used by the company, it cannot be denied that the procedure for retaining their clients’ data is time-consuming because client records are kept manually. Waw Mdp is a client record management system developed to save all client’s data in a database, preventing data loss that is common in traditional bookkeeping. The system was developed using the prototype model. A record management system would minimize data redundancy caused by manual data input, which is one of the desired outcomes of this system. This system has been able to help reduce the problems in handling data manually, such as data redundancy, loss of data and difficulties retrieving information. Finally, numerous enhancements can be made to the developed system to improve its usability, such as user interface improvement and notification function.